Modulation of IrO6 Chemical Environment for Highly Efficient Oxygen Evolution in Acid (Small 50/2022). Issue 50 (15th December 2022) - Zhao, Wenli; Xu, Fenghua; Wang, Zhaoyang; Pan, Zhipeng; Ye, Yiming; Hu, Shilin; Weng, Baicheng; Zhu, Rilong
Abstract : Highly Efficient Oxygen Evolution A facile strategy to incorporate Ir single atoms into the lattice of transition metal oxides is developed. The chemical environment of Ir and its neighboring oxygen are modulated, resulting in enhanced electrocatalytic oxygen evolution activity and durability. The electrocatalyst exhibits a mass activity of 1343.1 A g −1 and a turnover frequency of 0.04 s −1 . More details can be found in article number 2205495 by Baicheng Weng, Rilong Zhu, and co‐workers.